PENGARUH VARIASI BENTUK (SILINDER PENJAL DAN SILINDER BERONGGA), UKURAN PARTIKEL DAN TEKANAN TERHADAP KARAKTERISTIK PEMBAKARAN BRIKET LIMBAH ARANG ALABAN-SEKAM PADI - akhmad syarief; Fadliyanur; Dhanu Suryanta; Hansen Rivaldo Napitupulu; Aulia Aufa Ramadhasari; Defrihans Galang Putranto; Lukmanul Hakim (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2021)
The purpose of this study is to determine which shape of alaban bark charcoal waste briquettes is the most efficient according to its combustion characteristics. This research was conducted using experimental methods in the laboratory. It starts from filtering the charcoal waste, compressing into the wanted shapes and then combustion characteristics test. The manufactured briquettes are using 20 and 40 mesh of particle sizes, 50 kg/cm2 and 100 kg/cm2 holding pressure. The ratio between alaban charcoal waste and rice husk is 90 : 10, with 22 gram as the weight each. The shapes are solid cylinder and hollow cylinder. Combustion characteristic test used to determine the initial ignition, combustion rate and combustion temperatur. The results showed that hollow cylinder briquettes with 40 mesh particle size and 100 kg/cm2 holding pressure had the most efficient initial ignition and combustion rates with the combustion rate of 0,22 g/min. Meanwhile solid cylinder briquettes with 40 mesh particle size and 50 kg/cm2 holding pressure had the lowest initial ignition and combustion rates which is 0,14 g/min for the latter.